Kontribusi Mata Pelajaran Kewirausahaan Dan Pelaksanaan Praktik Kerja Lapangan Terhadap Minat Berwirausaha SiswaJurusan Akutansi SMK PGRI 4 Pedan Tahun Ajaran 2015/2016 - Hastutik, Ningrum Dwi; , Drs. Nur Chusni, SE, M.Ag (2016)
The purpose of this study was to determine: 1) Contributions eye entrepreneurial lesson to interest in entrepreneurship, 2) Contributions Implementation of job training to the interest in entrepreneurship, 3) Contributions subjects of entrepreneurship and job training Implementation of the interest in entrepreneurship. This research was quantitative kesimpulannnya. The population in this research were 81 students with asiswa 81 samples taken with random sampling technique. Necessary data obtained through the questionnaire method and documentation methods. Previous questionnaires have been tested and tested and tested reliabilitas.Teknik validity of data analysis used is multiple linear regression analysis, t-test, F, R2 test, the relative contribution and effective. Results of regression analysis regression equation: Y = 11.949 + 0,168X_110 + 0,336X_2 which means the subjects of entrepreneurship and implementation of field work practices contribute positively to students' interest in entrepreneurship. The conclusion is: 1) the subjects of entrepreneurship to contribute significantly to students' interest in entrepreneurship in the Accounting Department at SMK PGRI 4 PEDAN the academic year 2015/2016. Based on t test obtained t> t table is 2.431> 1.990 (α = 5%) and the significance value <0.05 is 0.017. 2) Implementation of job training contribute significantly to students' interest in entrepreneurship Accounting Department SMK PGRI 4 PEDAN the academic year 2015/2016. Based on t test obtained t> t table is 3.831> 1.990 (α = 5%) and the significance value <0.05 is 0.000. 3) Implementation of the subjects of entrepreneurship and job training contribute significantly to students' interest in entrepreneurship in the Accounting Department at SMK PGRI 4 PEDAN the academic year 2015/2016. Based on test results obtained Fhitung F> Ftable is 12.823> 3.109 at a significance level of 5%. 4) variable X1 gives the relative contribution of 32% and the effective contribution of 7.6%, X2 gives the relative contribution of 16% and the effective contribution of 23.6%. 5) The calculation result R2 obtained 0.236, which means the subjects of entrepreneurship and implementation of job training contributes to the $ 58.1% of the students' interest in entrepreneurship.